BRAND MANAGEMENT, ENTREPRENEURIAL MARKETING ORIENTATION, SOCIAL CAPITAL, RESOURCES CAPABILITIES AND ENVIRONMENTAL FACTORS IN SUSTAINING PERFOMANCE OF SMALL MEDIUM ENTERPRISES - Iin Mayasari; Adrian Azhar Wijanarko (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2020)
This study aims at exploring the concepts of 1) brand management and entrepreneurial marketing; 2) social capital and resources capability; 3) law and government as external environment. Entrepreneur performance is measured by both objective and subjective perspective. Objective perspective is measured by quantitative measurement and subjective perspective is measured by the perception of the ability to manage company. The method research was library study method.